Differences in Arbuscular Mycorrhizal Fungal Community Composition in Soils of Three Land Use Types in Subtropical Hilly Area of Southern China. - Caihuan Wang; Zhenhong Gu; Hang Cui; Honghui Zhu; Shenlei Fu; Qing Yao (PLoS ONE, 2015)
Land use type is key factor in restoring the degraded soils due to its impact on soil chemical properties and microbial community. In this study, the influences of land use type on arbuscular mycorrhizal fungal (AMF) community and soil chemical properties were assessed in a long-run experimental station in subtropical hilly area of southern China. Soil samples were collected from forest land, orchard and vegetable field. Soil chemical properties were analyzed, and PCR-DGGE was performed to explore the AMF community structure. Cloning and sequencing of DGGE bands were conducted to monitor AMF community composition. Results indicate that the contents of total P, available P and available K were the highest while the contents of soil organic matter, total N, total K and available N were the lowest in vegetable field soils, with forest land soils vice versa. According to DGGE profiling, AMF community in forest soils was more closely related to that in orchard soils than that in vegetable field soils. Sequencing indicated that 45 out of 53 excised bands were AMF and 64.4% of AMF belonged to Glomeraceae, including some "generalists" present in all soils and some "specialists" present only in soils of particular land use. Category principle component analysis demonstrated that total N, soil organic matter and available P were the most important factors affecting AMF community, and some AMF phylotypes were closely associated with particular soil chemical properties. Our data suggest that AMF communities are different with different land use types.